Disney princess storybook collection eaudiobook - Disney Press (Disney, 2016)
Get ready for an enchanting collection of stories, starring all the Disney Princesses! Solve a mystery with Rapunzel and the gang from the Snuggly Duckling. Gallop along with Merida after she meets a mysterious horse. Travel to Paris with Tiana as she competes in a global baking contest. Filled with wonder, excitement, and discovery, each princess's tale is a royal delight!